PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ( STUDI KASUS KONSUMEN TOKO TEKSTIL DAMAR PASAR TANAH ABANG ) - Tri Puji Rahayu; Alaidin Rapani; Riduan Siagian; Sofyan (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2023)
The purpose of this study is to determine the effect of product quality, price, and promotion on purchasing decisions in consumers of DAMAR textile stores. This study used a sample of 80 DAMAR store consumers who had made at least 2 purchases at DAMAR textile stores. The method used in this study is descriptive quantitative quantitatively. The data analysis technique used is Multiple Linear Regression Analysis using IBM SPSS Statistical 25 Software. The results of this study show that there is an influence between the variables of product quality, price, promotion of DAMAR textile stores simultaneously and significantly positive on textile purchasing decisions, this can be proven by the calculated value of 56,080 > 2.72 Ftabel and a sig value of 0.000 < 0.05 (α = 5%). Based on the results of the product quality variable t test and promotion with a significant positive impact on the textile purchase decision at the DAMAR store, this can be proven by the variable value of the calculated product quality of 4,030 > 1,991 ttabel with a significant value of 0.000 < 0.05 and the promotion variable of 4.965 > 1.991 ttabel 0.000 < 0.05. While the price variable has no significant effect on textile purchasing decisions, this can be proven by a calculated value of 0.769 < 1.991 ttabel 0.444 > 0.05 The result of the correlation of R of 0.830 means that there is a strong relationship between product quality, price, promotion to textile purchasing decisions in DAMAR stores, and for the Adjusted R Square determination correlation value of 0.677 or 67.7% means that the Independent variable together affects the bound variable by 67.7% and the remaining 32.3% is influenced by other variables that are not included in this study.